2011
DOI: 10.3171/2011.1.focus10262
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging in the assessment of ossification of the posterior longitudinal ligament: a report on preliminary results in 3 cases and review of the literature

Abstract: Cervical spondylotic myelopathy due to ossification of the posterior longitudinal ligament (OPLL) is a common neurosurgical disease that carries high morbidity. OPLL and other degenerative processes cause narrowing of the central canal, with subsequent spinal cord injury. Repeated minor trauma and vascular aberrations have been purported to underlie cervical spondylotic myelopathy, although the exact pathophysiological mechanism is unclear. Regardless, detection of early axonal damage may allow more ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…4 DTI is a reliable method for quantifying the microstructural abnormalities of the cervical spinal cord in patients with CSM, 5,[17][18][19] and many have suggested the correlation of DTI parameters with clinical severity. 20,21 In our previous study, we confirmed that DTI parameters of the cervical spinal cord in patients with high signal intensity were significantly different from those in healthy subjects. 22 DTI parameters and T2 high signal intensity are two different methods to evaluate the neurologic state of the spinal cord.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…4 DTI is a reliable method for quantifying the microstructural abnormalities of the cervical spinal cord in patients with CSM, 5,[17][18][19] and many have suggested the correlation of DTI parameters with clinical severity. 20,21 In our previous study, we confirmed that DTI parameters of the cervical spinal cord in patients with high signal intensity were significantly different from those in healthy subjects. 22 DTI parameters and T2 high signal intensity are two different methods to evaluate the neurologic state of the spinal cord.…”
Section: Discussionsupporting
confidence: 66%
“…[12][13][14][15] Diffusion tensor imaging (DTI) is considered to be more advantageous than conventional MRI because it can detect and quantify microstructural abnormalities. 5,[16][17][18][19] Recently, Jones et al 20 investigated the relationship between DTI parameters and clinical assessment in patients with CSM, and found that fractional anisotropy (FA) value correlated strongly with the modified Japanese Orthopedic Association (mJOA) score and Nurick score. Wen et al 21 showed not only that FA correlated positively with mJOA score, but it may also be indicative of surgical outcome with using logistic regression analysis.…”
Section: Introductionmentioning
confidence: 99%
“…30 The development of 3T scanners, reduction in artifact, and improvement in ROI selection methods and processing are yielding DTI indices that are better reflective of the microstructure of the spinal cord and its functional status. 34 , 35 Although we were able to note significant association between baseline mJOA scores and FA values obtained at both the LMC and high cervical cord at C1-2, other studies have noted a lesser relationship at the LMC. 29 This could be due to the aforementioned progress in DTI scanning technology.…”
Section: Discussionmentioning
confidence: 48%
“…3 Recent reports suggest that DTI may serve as a biomarker of spinal cord injury associated with CSM. [4][5][6][7] DTI parameterizes water diffusion within tissues and reports, among other metrics, the FA of the diffusion. FA represents an estimate of the directionality of water diffusion at the voxel level.…”
mentioning
confidence: 99%